2022
DOI: 10.1002/chem.202200360
|View full text |Cite
|
Sign up to set email alerts
|

A Stereocontrolled Total Synthesis of Lipoxin B4 and its Biological Activity as a Pro‐Resolving Lipid Mediator of Neuroinflammation

Abstract: Two stereocontrolled, efficient, and modular syntheses of eicosanoid lipoxin B4 (LXB4) are reported. One features a stereoselective reduction followed by an asymmetric epoxidation sequence to set the vicinal diol stereocentres. The dienyne was installed via a one‐pot Wittig olefination and base‐mediated epoxide ring opening cascade. The other approach installed the diol through an asymmetric dihydroxylation reaction followed by a Horner‐Wadsworth‐Emmons olefination to afford the common dienyne intermediate. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…Peak 15 had a [M + Na] + ion at m/z 375.2142, and its main fragment ion was at m/z 309.0986 ([M − C 3 H 7 ] + ). These results were characteristic of lipoxin B4 [38]. Peak 16 had a [M + H] + peak at m/z 299.1283 that generated a main fragment ion at m/z 91.0419 ([C 7 H 7 ] + ) and 77.0386 ([C 6 H 5 ] + ), which was characteristic of benzyl succinate [39].…”
Section: Uhplc-ms Analysismentioning
confidence: 98%
“…Peak 15 had a [M + Na] + ion at m/z 375.2142, and its main fragment ion was at m/z 309.0986 ([M − C 3 H 7 ] + ). These results were characteristic of lipoxin B4 [38]. Peak 16 had a [M + H] + peak at m/z 299.1283 that generated a main fragment ion at m/z 91.0419 ([C 7 H 7 ] + ) and 77.0386 ([C 6 H 5 ] + ), which was characteristic of benzyl succinate [39].…”
Section: Uhplc-ms Analysismentioning
confidence: 98%
“…A study focusing on molecular mechanisms showed that LXs analogues could enhance reprogramming and crosstalk between classical and non-classical innate immune cells, thus inducing the termination of the pro-inflammatory state and promoting the subsequent regression stage, which provided a possible treatment for inflammatory heart metabolic diseases [20]. In addition, research was performed for the asymmetric synthesis of four bicyclo-pentanes, including synthetic aromatic LXA4 mimetics, and the biological evaluation of analogues demonstrated the therapeutic potential of BCP-sLXms as a novel inflammatory regulator [63]. Moreover, it was found that the LXA4 analog BML-111 could reduce oxidative stress and glomerular podocyte injury by regulating the Nrf2 pathway [64].…”
Section: Anti-inflammatorymentioning
confidence: 99%
“…We recently demonstrated that LXA 4 is reduced in patient samples and attenuates T-cell activities and metabolism in a model of autoimmune uveitis [ 32 ]. Previously, we also reported on direct neuroprotective lipoxin actions using models of both retinal and cortical neurodegeneration, and demonstrated that the relevant synthetic circuit and receptor components are expressed in glial cells and neurons [ 33 , 34 ]. In particular, LXB 4 consistently exhibited more potent protective activities than LXA 4 [ 34 ].…”
Section: Introductionmentioning
confidence: 99%